2016
DOI: 10.1128/msphere.00227-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aspergillus fumigatus Isolates from Air and Surfaces of the International Space Station

Abstract: As durations of manned space missions increase, it is imperative to understand the long-term consequence of microbial exposure on human health in a closed human habitat. To date, studies aimed at bacterial and fungal contamination of space vessels have highlighted species compositions biased toward hardy, persistent organisms capable of withstanding harsh conditions. In the current study, we assessed traits of two independent Aspergillus fumigatus strains isolated from the International Space Station. Ubiquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 61 publications
8
98
0
Order By: Relevance
“…Nucleotide variant analysis of our four isolates, identified a total number of variations ranging from 48,590 to 68,352 compared to reference strain Af293. This range fits in the genetic diversity for A. fumigatus reported previously and determined in 95 sequences ranging from 36 - 72,000 SNPs (16). The large number of identified variants and differences in the genome structure displays a broad genetic diversity in the studied isolates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nucleotide variant analysis of our four isolates, identified a total number of variations ranging from 48,590 to 68,352 compared to reference strain Af293. This range fits in the genetic diversity for A. fumigatus reported previously and determined in 95 sequences ranging from 36 - 72,000 SNPs (16). The large number of identified variants and differences in the genome structure displays a broad genetic diversity in the studied isolates.…”
Section: Discussionsupporting
confidence: 87%
“…Some experimental infection studies have reported clinical isolates to be more virulent than environmental isolates (1315). Moreover, two environmental isolates retrieved from an International Space Station were more virulent than the experimental strains Af293 and CEA10 (16). Additionally, an in-host study that analyzed the microevolution of 13 isogenic isolates of A. fumigatus obtained from the same patient over a period of 2 years, reported both increases and decreases in virulence among the isolates (17).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the genomes of 66 globally distributed strains of Aspergillus fumigatus for polymorphisms in SM gene clusters. We performed whole-genome sequencing on 8 strains, and collected the remaining 58 strains from publicly available databases including NCBI Genome and NCBI Short Read Archive (Figure 1, (Table S1) [2832]. All publicly available strains of A. fumigatus with sequencing data passing quality thresholds (see Methods) or with assembled genomes were included in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The strains used included both environmental and clinical strains and were isolated from multiple continents. Genome assemblies for 10 of these strains, including the Af293 and A1163 reference strains, were available for download from GenBank [2832,70]. For 6 of these strains, short read sequences were also available from the NCBI Short Read Archive (SRA), which were used for variant discovery only (see Single nucleotide variant (SNV) and indel discovery) and not for genome assembly.…”
Section: Methodsmentioning
confidence: 99%
“…These results are in agreement with studies in A. fumigatus that have described great strain heterogeneity in traits such as growth, fitness and enzyme secretion between different environmental and clinical isolates (24, 37). Indeed, the number of SNPs, obtained during strain pairwise comparison, in the genomes of different A. fumigatus strains, range between ~13,500 (24) and ~50,000 (38, 39). Strain heterogeneity has therefore mainly been investigated in environmental and clinical isolates of A. fumigatus, whereas similar studies have not been carried out for A. nidulans isolates.…”
Section: Resultsmentioning
confidence: 99%